Worker Power, Immigrant Sorting, and Firm Dynamics - Mikko Silliman; Alexander Willén (Institute of Labor Economics (IZA), 2024)
This paper combines two of the most central features of modern labor markets —immigrants and unions — to examine the role of worker power in shaping immigrant sorting across firms, and how that subsequently influences the performance of firms and the careers of incumbent workers. First, unions push immigrants to enter lower-paying and lower-quality firms with weaker union representation. Second, these firms with weaker union representation are able to use the cheaper immigrant labor to scale up production, thereby out-competing firms with stronger union representation and capturing market share. Third, incumbent workers in firms with weaker union representation benefit by shifting into management positions and capturing some of the firm's increased rents. Fourth, despite benefiting incumbent workers in firms with weaker union representation, these workers are more likely to become union members themselves in response to greater contact with new immigrants. Broadly, our results cut across nearly all sectors but are considerably more muted in competitive markets.
Keywords: J2; J3; J5; J6; 330; immigration; worker power; unions; firms